Rejection of Village Change into Village: A Case Study in Banyumas and Tangerang Districts - Giyanto, Bambang; Murtinah, Tintin Sri; Habibi, Nuh (KnE Social Sciences, 2022)
This research examined village change rejection using the case study of Banyumas and Tangerang villages. A qualitative approach was used. The findings were as follows: a) Institutional aspects – in villages that reject changes, it is feared that the village community will lose the rights of the village that had previously existed; b) Human resources aspects – all villages rejected when there was a change of status to village because the villagers would not have the opportunity to become a village device, and it is a source of pride for the village community if it becomes a village device; c) Local wisdom aspects – all of the studied villages rejected the conversion into a village, because the village has full autonomy in terms of budget control; d) Public services aspects – the village community is more comfortable in the services provided by the village because these are provided in 24 hours, whereas otherwise this is not the case because the device is not local villagers; and e) Local wisdom values aspects – the village community is more comfortable. According to the findings of the study, the village should remain a village and should not be forced to change. The most important thing is to increase the capacity of village devices and provide village government with management support. Keywords: rejection, village, districts